A revision of the Xestia (Radddea) alexis (Kozhanchikov, 1928) species-group with a checklist of subgenus Raddea Alphéraky, 1892 and description of brachipterous females (Lepidoptera, Noctuidae, Noctuinae) - Kononenko, Vladimir S.; Volynkin, Anton V.; Matov, Alexei Yu. (Zootaxa, 2012)
The subgenus Raddea Alphéraky, 1892 of the genus Xestia Hübner, 1818 is reviewed. A checklist of 29 described species is presented, with 26 new combinations (comb. n.) introduced. Two taxa, Xestia (Raddea) alexis (Kozhanchikov, 1928) and Xestia (Raddea) herrichschaefferi (Alphéraky, 1895) are revised, and three new synonyms are introduced (X. alexis (Kozhanchikov, 1928) = Estimata oschi Kozhanchikov, 1937, syn. n.; = Estimata militzae Kozhanchikov, 1937 syn. n.; Protolampra sobrina (Duponchel, 1843) = Estimata dailingensis Chen, 1984, syn. n.). The name alexis Kozhanchikov, 1937 is recognized as unjustified emendation. Lectotypes for X. alexis and X. herrichschaefferi are designated; brachypterous females for X. alexii and X. herrichschaefferi are described.